Cannabis Use Among Mental Health Professionals: A Qualitative Study of Cannabis-Related Risk Perceptions - Ghelani, Amar (Journal of drug issues, 2021)
Background: Perceptions of cannabis-related risk are changing, and many are viewing cannabis as harmless despite the biopsychosocial risks. Perceptions of risk have an impact on behavior as individuals who are less likely to view cannabis as risky are more likely to use it problematically. Purpose: This study examined how mental health professionals who use cannabis perceive the risks related to use. Methods: Interpretative phenomenological analysis was utilized to understand how participants made sense of the harm related to personal and client use. Interviews were conducted with a sample of social workers, nurses, and psychotherapists who work with cannabis-consuming clients. Results: Participants reported cannabis use is related to anxiety, relational challenges, impaired driving, psychosis, cognitive impairment, educational/employment dysfunction, and addiction in some users. Conclusion: Assessing risk perceptions among cannabis users can reveal subtle psychosocial problems the user may be experiencing. Mental health workers may benefit from further education regarding cannabis-related physical health harm.